2015
DOI: 10.18632/oncotarget.3598
|View full text |Cite
|
Sign up to set email alerts
|

Large oncosomes contain distinct protein cargo and represent a separate functional class of tumor-derived extracellular vesicles

Abstract: Large oncosomes (LO) are atypically large (1-10μm diameter) cancer-derived extracellular vesicles (EVs), originating from the shedding of membrane blebs and associated with advanced disease. We report that 25% of the proteins, identified by a quantitative proteomics analysis, are differentially represented in large and nano-sized EVs from prostate cancer cells. Proteins enriched in large EVs included enzymes involved in glucose, glutamine and amino acid metabolism, all metabolic processes relevant to cancer. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
340
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 311 publications
(378 citation statements)
references
References 60 publications
22
340
2
3
Order By: Relevance
“…L-EVs were isolated from U2OS cells (osteosarcoma cell line) stably transfected with a GFP-conjugated histone H2B (U2OS-H2B-GFP). GFP signal was detected in purified L-EVs (Figure S1A, B) in line with previous identification of histones in EVs [24,32]. In L-EVs stained with Hoechst, a fluorescent dye that binds to the minor groove of dsDNA (Fig.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…L-EVs were isolated from U2OS cells (osteosarcoma cell line) stably transfected with a GFP-conjugated histone H2B (U2OS-H2B-GFP). GFP signal was detected in purified L-EVs (Figure S1A, B) in line with previous identification of histones in EVs [24,32]. In L-EVs stained with Hoechst, a fluorescent dye that binds to the minor groove of dsDNA (Fig.…”
Section: Resultssupporting
confidence: 89%
“…In order to determine if we could use L-EVs and S-EVs as surrogates for LO and Exo, we tested expression of specific markers of LO and Exo, obtained by floatation of L-EVs and S-EVs in discontinuous density gradients [24]. L-EVs expressed LO markers CK18 and HSPA5 [24], and S-EVs expressed CD81, which is typically enriched in Exo [3], suggesting that we can use L- and S-EVs as surrogates for LO and Exo (Figure 3(b)).
10.1080/20013078.2018.1505403-F0001Figure 1. Most extracellular DNA is packaged into L-EVs . (a) Tunable resistive pulse sensing (TRPS, qNano) using two different pore membranes (NP4000 and NP200) identified as L-EVs (left) and S-EVs (right) derived from PC3 cells.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that our EV isolation procedure (filtration through 0.22 microns, and ultracentrifugation at 10,000 × g) removed most of the large EVs from the sample, and enrich in small EVs (mostly exosomes and small microvesicles), this difference could be underestimated in our samples. Importantly, in agreement with our result, it has already been reported that prostate cancer cells release large EVs named oncosomes with a size between 1 and 10 microns [31] that contain a distinct protein cargo [32]. They have also been detected in circulation in models of PCa and shown that their abundance correlate with tumoral progression [31].…”
Section: Discussionsupporting
confidence: 92%